E-Storybooks as Supplementary Material for Fourth Grade Elementary School Students - Luh Dewi Asih; GAP Suprianti; Luh Gede Eka Wahyuni (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
The source of English learning materials used at school was only textbook without any supplementary materials. Supplementary materials in English teaching and learning process are considered as one of the ways to engage students in learning. This study aims to develop e-storybooks for fourth-grade pupils as supplementary materials based on the Merdeka curriculum. This Design and Development study used the ADDE model as proposed by Richey and Klein (2014). Qualitative and quantitative approach were used to analyze both non numerical and numerical data sequentially. English teacher and grade four students were involved as the subject of this study. Experts and user who validated the e-storybooks gave an overall score of 5 that showed the developed e-storybooks was the “Excellent Product” and valid to be used. Therefore, the developed e-storybooks can be used by grade four students to learn English in fun and interactive way. As these e-storybooks have various components that match to the students’ needs and the current curriculum, teacher was suggested to utilize it as the supplementary materials in English teaching and learning process.